The bones of grace - Anam, Tahmima (Edinburgh : Canongate Books, 2016)
The highly acclaimed romantic tragedy of love, migration, and the search for identity from the Granta 'Best of Young British' author
First published: Edinburgh : Canongate Books Ltd, 2016
ENH
Trim Education
Keywords: Self-actualization (Psychology) in women -- Fiction; Self-realization in women -- Fiction; Culture conflict -- Fiction